How outcome uncertainty, loss aversion and team quality affect stadium attendance in Dutch professional football - Lucas Besters; Jan C. van Ours; Martin A. van Tuijl (Tinbergen Institute, 2018)
We investigate stadium attendance in the highest level of Dutch professional football for the seasons 2000/01 – 2015/16 focusing on outcome uncertainty, loss aversion and team quality. We find that for individual football matches, attendance is related to reference-dependent preferences with loss aversion dominating the preference for uncertain outcomes. Furthermore, team quality is an important determinant of stadium attendance. Towards the end of the season, outcome uncertainty regarding the final ranking becomes important. For this seasonal uncertainty, we find a positive and stable, but rather small impact of the introduction of a unique and large end-of-season play-off scheme for the qualification for European football.
Keywords: Z20; L83; D12; 330; Stadium attendance; Professional football; Outcome uncertainty; Loss aversion; Play-offs